A solution and process for improving the corrosion resistance of fasteners made of PH13-8Mo material

By using a solution process containing nitric acid, corrosion inhibitor and other components, free iron on the surface of the fastener made of PH13-8Mo material is removed, and chromate and hydrophobic protective film are formed, which solves the problem that the material is under a high humidity and high salt environment. The poor corrosion resistance problem significantly reduces the risk of corrosion and fracture and meets the strict inspection standards of aerospace fasteners.

CN119144962BActive Publication Date: 2025-02-11ORIENTAL BLUE SKY TITANIUM TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411657634.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-02-11
Estimated Expiration
2044-11-20

AI Technical Summary

Technical Problem

Fasteners made of PH13-8Mo material have poor corrosion resistance in high humidity and high salt environments, resulting in high risk of corrosion and fracture, making it difficult to meet the strict inspection standards of aerospace fasteners.

Method used

Using a solution process containing component A, component B and component C, component A removes free iron through nitric acid and other components, component B forms a dense chromate protective film, and component C forms a hydrophobic protective film. Improve the corrosion resistance of parts.

Benefits of technology

It significantly improves the corrosion resistance of PH13-8Mo fasteners in high humidity and high salt environments, reduces the risk of corrosion and fracture, and enhances the reliability and safety of aerospace fasteners.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119144962B_ABST
    Figure CN119144962B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of aerospace fastener processing, and specifically relates to a solution and process for improving the corrosion resistance of fasteners made of PH13-8Mo material, the solution includes component A, component B and component C, and the component A includes, by mass percentage, nitric acid 35-40%; corrosion inhibitor 3-5%; stabilizer 3-5%; surfactant 2-4%; dispersant 2-4%; solvent remainder; by mass percentage, the component B includes: boric acid 5-10%; film former 10-15%; complexing agent 8-10%; oxidant 8-10%; thickener 5-10%; wetting agent 3-5%; solvent remainder; by mass percentage, component C includes: emulsifier 4-8%; surfactant 12-15%; rust inhibitor 18-25%; solvent remainder. The present invention forms a protective film after removing free iron from the surface of the part, improves the protective effect on the part, and thus improves the corrosion resistance of the part.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a solution and a process for improving the corrosion resistance of a fastener made of PH13-8Mo material, and belongs to the technical field of aerospace fastener processing. Background Art

[0002] At present, the fasteners widely used in the aerospace field are generally made of alloy steel or stainless steel materials, such as 45# steel, 30CrMnSiA, 1Cr18Ni9Ti, etc. These traditional materials are difficult to meet the requirements of new models for fastener strength or corrosion resistance. There are many problems and hidden dangers in the use process, such as hydrogen embrittlement and insufficient fatigue performance. In addition, traditional steel fasteners usually use electroplating surface treatment, which has poor corrosion resistance and is prone to electroplating brittleness, causing great pollution to the environment. With the development of aerospace models and the research and development of heavy-duty carrier models, the aerospace field has put forward requirements for fasteners such as high temperature resistance, corrosion resistance, weight reduction, and reliability, which has prompted various aerospace models to use a new type of stainless steel-PH13-8Mo material. PH13-8Mo material is a precipitation hardened stainless steel with high strength, high hardness, high temperature resistance, corrosion resistance, good ductility and toughness, and can withstand large impact loads. PH13-8Mo material is used as

[0003] The substrate of aerospace fasteners has many advantages, but during the fastener molding process, free iron may be introduced into the surface of the PH13-8Mo substrate, making its corrosion resistance in high humidity and high salt environments worse. Therefore, how to maximize the corrosion resistance of PH13-8Mo aerospace fasteners without affecting the material's strength, hardness and other metallurgical properties, so that it can meet the requirements of the increasingly stringent inspection standards for aerospace fasteners, reduce the risk of fastener corrosion and fracture, reduce the occurrence of safety accidents, and assist in the launch of new models is a technical problem that technicians in this field urgently need to solve. Summary of the invention

[0004] In view of the above problems in the prior art, the present invention provides a solution and a process for improving the corrosion resistance of fasteners made of PH13-8Mo material.

[0005] The technical solution of the present invention to solve the above technical problems is as follows:

[0006] One of the purposes of the present invention is to provide a solution for improving the corrosion resistance of fasteners made of PH13-8Mo material, which comprises component A, component B and component C.

[0007] In terms of mass percentage, the component A includes: 35-40% nitric acid; 3-5% corrosion inhibitor; 3-5% stabilizer; 2-4% surfactant; 2-4% dispersant; and the remainder solvent;

[0008] In terms of mass percentage, the component B includes: 10-15% film former; 8-10% complexing agent; 8-10% oxidant; 5-10% boric acid; 5-10% thickener; 3-5% wetting agent; and the remainder of solvent;

[0009] Calculated by mass percentage, the component C includes: 4-8% emulsifier; 12-15% surfactant; 18-25% rust inhibitor; and the remainder solvent.

[0010] The beneficial effects of the solution for improving the corrosion resistance of fasteners made of PH13-8Mo material of the present invention are:

[0011] The present invention adds nitric acid to component A for removing active metals such as free iron and other pollutants on the surface of the product, and adds components such as corrosion inhibitors, stabilizers, surfactants and dispersants to improve the rust removal stability of component A, thereby improving the corrosion resistance of parts; the present invention adds a film-forming agent to component B, which can further remove rust from the surface of the product, improve the finish and brightness, and form a dense chromate protective film to isolate the base metal from oxygen and play an anti-corrosion role; the addition of a complexing agent, an oxidant and boric acid can further improve the anti-corrosion effect, and the ratio of a thickener and a wetting agent provides a better film-forming environment for the formation of the protective film; the present invention adds an emulsifier, a surfactant and a rust inhibitor to component C, so that a hydrophobic protective film is formed on the surface of the part, thereby improving the protective effect of the film layer on the part.

[0012] On the basis of the above technical solution, the present invention can also make the following improvements:

[0013] Furthermore, in the component A, the corrosion inhibitor is ammonium nitrate; the stabilizer is citric acid; the surfactant is sodium fatty alcohol polyoxyethylene ether sulfate; and the dispersant is acetylene glycol.

[0014] Furthermore, in the component B, the film-forming agent is chromium nitrate; the complexing agent is succinic acid; the oxidizing agent is sodium nitrate; the thickening agent is triethanolamine; and the wetting agent is sodium dodecyl sulfate.

[0015] Furthermore, in the component C, the emulsifier is nonylphenol polyoxyethylene ether; the surfactant is polyoxyethylene fatty alcohol ether; and the rust inhibitor is barium petroleum sulfonate and N-oleoyl sarcosine octadecyl ammonium salt.

[0016] Furthermore, the solvent is water.

[0017] The second object of the present invention is to provide a process for improving the corrosion resistance of fasteners made of PH13-8Mo material, using the above-mentioned solution for improving the corrosion resistance of fasteners made of PH13-8Mo material, specifically comprising the following steps:

[0018] (1) Place the parts in a perforated container and soak the container in component A at room temperature, with a soaking temperature of 45°C-55°C and a soaking time of 30min-40min. Shake the container 3-4 times during the soaking period.

[0019] (2) Use running cold water to clean the residual component A on the surface of the parts, shaking the container for 0.5 min to 1.0 min;

[0020] (3) Immerse the parts in deionized water, shaking the container for 0.5 min to 1.0 min;

[0021] (4) First use compressed air to clean the surface water of the parts, and then dry them at a temperature of 80°C-100°C for 20min-30min;

[0022] (5) Soak the parts in component B at a temperature of 60°C-70°C for 15-20 minutes, shaking the container 3-4 times during the soaking period;

[0023] (6) Use running cold water to clean the component B remaining on the surface of the parts, shaking the container during the process, for 1.0 min to 3.0 min;

[0024] (7) Immerse the parts in deionized water, shaking the container for 1.0 min to 3.0 min;

[0025] (8) First use compressed air to clean the surface water of the parts, and then dry them at a temperature of 130°C-135°C for 15min-20min;

[0026] (9) Soak the parts in component C for 2-3 minutes, shaking the container 1-2 times during the soaking period;

[0027] (10) Place the parts in an oven at a drying temperature of 80°C-120°C and a drying time of 20 min-30 min.

[0028] Furthermore, the container is a titanium basket.

[0029] Furthermore, in step (1), the amount of parts loaded is less than or equal to 1 / 3 of the volume of the container.

[0030] Furthermore, in step (4) and step (8), the parts are dried in an electric heated blast drying oven.

[0031] The beneficial effects of the solution for improving the corrosion resistance of fasteners made of PH13-8Mo material of the present invention are:

[0032] The present invention sequentially immerses parts in component A, component B and component C, first removes active metals such as free iron and other pollutants on the product surface in component A, then further removes rust on the product surface in component B to improve smoothness and brightness, and can form a dense chromate protective film to isolate the base metal from oxygen and play an anti-corrosion role, and then forms a hydrophobic protective film in component C to further improve the protection of the part surface, improve the corrosion resistance of the part in a high-humidity and high-salt environment, reduce the risk of corrosion and fracture of the part, and reduce the occurrence of aerospace safety accidents. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 The photos of pH13-8Mo hexagonal head bolts before and after the salt spray test of Example 1 are shown;

[0034] Figure 2 The photos of pH13-8Mo hexagonal head bolts before and after the salt spray test of Example 2 are shown;

[0035] Figure 3 The photos of pH13-8Mo hexagonal head bolts before and after the salt spray test of Example 3 are shown;

[0036] Figure 4 This is a photo of the corrosion depth after metallographic inspection of Comparative Example 1;

[0037] Figure 5 The photos of pH13-8Mo hexagonal head bolts before and after the salt spray test of Comparative Example 2 are shown;

[0038] Figure 6 The photos of pH13-8Mo hexagonal head bolts before and after the salt spray test of Comparative Example 3 are shown;

[0039] Figure 7 The photos of pH13-8Mo hexagonal head bolts before and after the salt spray test of Comparative Example 4 are shown;

[0040] Figure 8 The photos of pH13-8Mo hexagonal head bolts before and after the salt spray test of Comparative Example 5 are shown;

[0041] Fig. 9 This is a photo of the pH13-8Mo hexagonal head bolt after being taken out from component A in comparative example 6;

[0042] Fig.10 The photos of pH13-8Mo hexagonal head bolts before and after the salt spray test of Comparative Example 7 are shown;

[0043] Fig.11 The photos of pH13-8Mo hexagonal head bolts before and after the salt spray test of Comparative Example 8 are shown;

[0044] Fig.12This is a corrosion photo of Comparative Example 9 after metallographic inspection;

[0045] Fig.13 Photos of pH13-8Mo hexagonal head bolts before and after the salt spray test of Comparative Example 10;

[0046] Fig.14 Photos of pH13-8Mo hexagonal head bolts before and after the salt spray test of Comparative Example 11;

[0047] Fig.15 This is a photo of the pH13-8Mo hexagonal head bolt after being taken out from component C in comparative example 12;

[0048] Fig.16 This is a picture of the solution of component C in Comparative Example 13. DETAILED DESCRIPTION

[0049] The principles and features of the present invention are described below in conjunction with the accompanying drawings. The examples given are only used to explain the present invention and are not used to limit the scope of the present invention.

[0050] Example 1

[0051] The solution for improving the corrosion resistance of fasteners made of PH13-8Mo material in this embodiment includes the following components:

[0052] Component A:

[0053]

[0054] Component B:

[0055]

[0056] Component C:

[0057]

[0058] The implementation process of improving the corrosion resistance of the fastener made of PH13-8Mo material in this embodiment is as follows:

[0059] (1) Place the parts in a titanium basket with the basket volume not exceeding 1 / 3 of the basket volume. Soak the titanium basket in component A at room temperature for 30 min. Set the temperature to 45°C and shake the titanium basket every 10 minutes or so to ensure that the grooves, gaps and other parts of the parts are fully exposed to the solution.

[0060] (2) Take out the titanium basket, clean the component A remaining on the surface of the parts with running cold water, and shake the titanium basket lightly and evenly for 0.5 min.

[0061] (3) Immerse the parts in deionized water and shake the titanium basket gently and evenly for 0.5 min.

[0062] (4) Take out the titanium basket, first use compressed air to quickly clean the surface water of the parts, and then dry them in an electric blast drying oven at 80°C for 20 minutes.

[0063] (5) Soak the parts in component B at 60°C for 15 minutes. Shake the titanium basket evenly and gently every 5 minutes to ensure that all surfaces of the parts are in full and even contact with the solution.

[0064] (6) Take out the titanium basket, clean the component B remaining on the surface of the parts with running cold water, and shake the titanium basket lightly and evenly for 1 minute.

[0065] (7) Immerse the parts in deionized water and shake the titanium basket gently and evenly for 1 minute.

[0066] (8) Take out the titanium basket, first use compressed air to quickly clean the surface water of the parts, and then dry them in an electric blast drying oven at 130°C for 15 minutes.

[0067] (9) Soak the parts in component C at room temperature for 2 minutes, and shake the titanium basket slightly and evenly once every 1 minute.

[0068] (10) Take out the titanium basket and place the parts in an oven at 80°C for 20 minutes.

[0069] Product corrosion resistance assessment method - salt spray test

[0070] According to GJB 150.11A-2009 "Military Equipment Laboratory Environmental Test Method Part 11: Salt Spray Test", the dry-wet alternating test (hereinafter referred to as GJB150.11) is carried out, and the mass concentration of the salt solution is controlled to be 5%±1%, the pH value is 6.5-7.2, and the temperature in the salt spray chamber is 35℃±2℃. The test should use a test procedure of alternating 24h salt spray and 24h drying for a total of 96h (2 spray wet stages and 2 dry stages). Experience has shown that this alternating method and test time can provide salt spray test results that are closer to the actual exposure situation than continuous spray for 96h, and have greater potential destructiveness, because the corrosion rate is higher during the transition from wet state to dry state.

[0071] In order to verify the effect of the solution of this example on the corrosion resistance of aerospace fasteners made of PH13-8Mo material, the test was stricter than the original standard requirements, the test time was extended, and a test procedure of alternating 24 hours of salt spray and 24 hours of drying for a total of 192 hours (4 spray wetting stages and 4 drying stages) was used.

[0072] During the test, the hanging direction of the bolts should be kept consistent to avoid contact between specimens and to prevent the salt solution dripping from the bolts from dripping onto other bolts.

[0073] In this embodiment, the parts used in the test are pH13-8Mo hexagonal head bolts. After the pH13-8Mo hexagonal head bolts of this embodiment are treated by the process and solution of this embodiment, a dry-wet alternating salt spray test is performed according to GJB150.11. After 192 hours, no rust appears on the surface of the pH13-8Mo hexagonal head bolts. Figure 1 Among them, the upper and lower groups are the hexagon head bolts before and after the dry-wet alternating salt spray test.

[0074] Embodiment 2:

[0075] Component A:

[0076]

[0077] Component B:

[0078]

[0079] Component C:

[0080]

[0081] The implementation process of improving the corrosion resistance of the fastener made of PH13-8Mo material in this embodiment is as follows:

[0082] (1) Place the parts in a titanium basket with the basket volume not exceeding 1 / 3 of the basket volume. Soak the titanium basket in component A at room temperature for 40 min. Set the temperature to 55°C and shake the titanium basket every 10 minutes or so to ensure that the grooves, gaps and other parts of the parts are fully exposed to the solution.

[0083] (2) Take out the titanium basket, clean the component A remaining on the surface of the parts with running cold water, and shake the titanium basket lightly and evenly for 1 minute.

[0084] (3) Immerse the parts in deionized water and shake the titanium basket gently and evenly for 1 minute.

[0085] (4) Take out the titanium basket, first use compressed air to quickly clean the surface water of the parts, and then dry them in an electric blast drying oven at a temperature of 100°C for 30 minutes.

[0086] (5) Soak the parts in component B at 70°C for 20 minutes. Shake the titanium basket evenly and gently every 5 minutes to ensure that all surfaces of the parts are in full and even contact with the solution.

[0087] (6) Take out the titanium basket, clean the component B remaining on the surface of the parts with running cold water, and shake the titanium basket lightly and evenly for 3 minutes.

[0088] (7) Immerse the parts in deionized water and shake the titanium basket gently and evenly for 3 minutes.

[0089] (8) Take out the titanium basket, first use compressed air to quickly clean the surface water of the parts, and then dry them in an electric blast drying oven at a temperature of 135°C for 20 minutes.

[0090] (9) Soak the parts in component C at room temperature for 3 minutes, and shake the titanium basket slightly and evenly once every 1 minute.

[0091] (10) Take out the titanium basket and place the parts in an oven at 120°C for 30 minutes.

[0092] In this embodiment, the parts used in the test are pH13-8Mo hexagonal head bolts. After the pH13-8Mo hexagonal head bolts of this embodiment are treated by the process and solution of this embodiment, a dry-wet alternating salt spray test is performed according to GJB150.11. After 192 hours, no rust appears on the surface of the pH13-8Mo hexagonal head bolts. Figure 2 Among them, the upper and lower groups are the hexagon head bolts before and after the dry-wet alternating salt spray test.

[0093] Embodiment 3:

[0094] Component A:

[0095]

[0096] Component B:

[0097]

[0098] Component C:

[0099]

[0100] The implementation process of improving the corrosion resistance of the fastener made of PH13-8Mo material in this embodiment is as follows:

[0101] (1) Place the parts in a titanium basket with the basket volume not exceeding 1 / 3 of the basket volume. Soak the titanium basket in component A for 35 min at room temperature. Set the temperature to 50°C and shake the parts every 10 minutes or so to ensure that the grooves, gaps and other parts of the parts are fully exposed to the solution.

[0102] (2) Take out the titanium basket, clean the component A remaining on the surface of the parts with running cold water, and shake the titanium basket lightly and evenly for 50 seconds.

[0103] (3) Immerse the parts in deionized water and shake the titanium basket gently and evenly for 50 seconds.

[0104] (4) Take out the titanium basket, first use compressed air to quickly clean the surface water of the parts, and then dry them in an electric blast drying oven at 90°C for 25 minutes.

[0105] (5) Soak the parts in component B at 65°C for 17 minutes. Shake the titanium basket evenly and gently every 5 minutes to ensure that all surfaces of the parts are in full and even contact with the solution.

[0106] (6) Take out the titanium basket, clean the component B remaining on the surface of the parts with running cold water, and shake the titanium basket lightly and evenly for 2 minutes.

[0107] (7) Immerse the parts in deionized water and shake the titanium basket gently and evenly for 2 minutes.

[0108] (8) Take out the titanium basket, first use compressed air to quickly clean the surface water of the parts, and then dry them in an electric blast drying oven at a temperature of 132°C for 17 minutes.

[0109] (9) Soak the parts in component C at room temperature for 2.5 minutes, and shake the titanium basket slightly and evenly once every 1 minute.

[0110] (10) Place the parts in an oven at 100°C and dry for 25 minutes.

[0111] In this embodiment, the parts used in the test are pH13-8Mo hexagonal head bolts. After the pH13-8Mo hexagonal head bolts of this embodiment are treated by the process and solution of this embodiment, a dry-wet alternating salt spray test is performed according to GJB150.11. After 192 hours, no rust appears on the surface of the pH13-8Mo hexagonal head bolts. Figure 3 Among them, the upper and lower groups are the hexagon head bolts before and after the dry-wet alternating salt spray test.

[0112] Comparative Example 1:

[0113] Compared with Example 1, the treatment process of this comparative example remains unchanged, and the ingredients and concentrations of component B and component C remain unchanged. The difference is that ammonium nitrate is not added to component A of this comparative example.

[0114] From the metallographic test results, it can be seen that since ammonium nitrate was not added to component A in this comparative example, the pH13-8Mo matrix was corroded by the strong oxidant nitric acid. The metallographic microscope magnified 200 times and the obvious corrosion depth could be observed. Figure 4 .

[0115] Comparative Example 2:

[0116] Compared with Example 1, the treatment process of this comparative example remains unchanged, and the ingredients and concentrations of component B and component C remain unchanged. The difference is that the content of acetylene glycol in component A is reduced to 10 ml.

[0117] From the results of the salt spray test, it can be seen that in this comparative example, the content of acetylene glycol in component A is reduced, resulting in poor dispersibility of the solution and incomplete oxidation of non-inert metal elements on the surface of the product. After 22 hours of the salt spray test, slight red pitting appeared on the thread of one bolt, see Figure 5 .

[0118] Comparative Example 3:

[0119] Compared with Example 2, the treatment process of this comparative example remains unchanged, the ingredients and concentrations of component B and component C remain unchanged, and the difference is that the citric acid content in component A is increased to 60 ml.

[0120] From the results of the salt spray test, it can be seen that due to the increase in the citric acid content in component A in this comparative example, the uniformity and density of the formed oxide film layer are reduced. After 72 hours of the salt spray test, rust spots began to appear on the six sides of the bolt head. Figure 6 Among them, the upper and lower groups are the hexagon head bolts before and after the dry-wet alternating salt spray test.

[0121] Comparative Example 4:

[0122] Compared with Example 1, the treatment process of this comparative example remains unchanged, the composition and concentration of component B and component C remain unchanged, and the difference is that the nitric acid content in component A is reduced to 300 ml.

[0123] From the results of the salt spray test, it can be seen that since the nitric acid content in component A in this comparative example is reduced, the free iron introduced by machining on the surface of the pH13-8Mo bolt cannot be completely removed, and the surface of the product is not completely inert. After 17 hours of salt spray test, six sides of the bolt head, the polished rod, and the threaded parts all show severe reddish-brown rust, see Figure 7 Among them, the upper and lower groups are the hexagon head bolts before and after the dry-wet alternating salt spray test.

[0124] Comparative Example 5:

[0125] Compared with Example 1, in the solution of this comparative example, the composition and concentration of components A, B, and C remain unchanged. The difference is that during the treatment process in this comparative example, the immersion temperature of the parts in component A is reduced from 45°C to room temperature, and the solution temperature of component B is reduced from 60°C to 50°C.

[0126] From the results of the salt spray test, it can be seen that due to the decrease in the solution temperature of component A and component B in this comparative example, the reaction rate between the solution and the free iron and other substances on the surface of the product is reduced. After 24 hours of the salt spray test, slight rust appeared on the six sides of the bolt head. Figure 8 Among them, the upper and lower groups are the hexagon head bolts before and after the dry-wet alternating salt spray test.

[0127] Comparative Example 6:

[0128] Compared with Example 2, the treatment process of this comparative example remains unchanged, the ingredients and concentrations of component B and component C remain unchanged, and the difference is that the amount of fatty alcohol polyoxyethylene ether sodium sulfate in component A is increased to 50 ml.

[0129] It can be seen from the operation process that in this comparative example, the amount of surfactant in component A is increased, resulting in poor solution operation performance. During the dipping and shaking process, a large amount of foam adheres to the product surface, affecting the treatment effect. Fig. 9 .

[0130] Comparative Example 7:

[0131] Compared with Example 1, the treatment process of this comparative example remains unchanged, the composition and concentration of component A and component C remain unchanged, and the difference is that the amount of chromium nitrate in component B is reduced to 90 ml.

[0132] From the results of the salt spray test, it can be seen that since the amount of film-forming agent in component B in this comparative example is reduced, the corrosion-resistant oxide film is not fully formed and has poor stability. After 48 hours of the salt spray test, six sides of the bolt head, the polished rod, and the threaded parts all show severe reddish-brown rust. Fig.10 Among them, the upper and lower groups are the hexagon head bolts before and after the dry-wet alternating salt spray test.

[0133] Comparative Example 8:

[0134] Compared with Example 1, the treatment process of this comparative example remains unchanged, the ingredients and concentrations of component A and component C remain unchanged, and the difference is that the amount of boric acid in component B is reduced to 40 ml.

[0135] From the results of the salt spray test, it can be seen that in this comparative example, the amount of boric acid used to assist film formation in component B is reduced, resulting in an incomplete oxide film layer on the surface of the pH13-8Mo bolt and poor corrosion resistance. After 24 hours of the salt spray test, reddish-brown rust appeared on the six sides of the bolt head and the bare rod. Fig.11 Among them, the upper and lower groups are the hexagon head bolts before and after the dry-wet alternating salt spray test.

[0136] Comparative Example 9:

[0137] Compared with Example 2, the treatment process of this comparative example remains unchanged, the ingredients and concentrations of component A and component C remain unchanged, and the difference is that the amount of sodium nitrate in component B is increased to 110 ml.

[0138] From the metallographic test results, it can be seen that due to the increase in the amount of oxidant sodium nitrate in component B in this comparative example, excessive corrosion occurred on the surface of the pH13-8Mo bolt. When the metallographic examination was magnified 200 times, it can be observed that there are many obvious corrosion depths on the surface of the product, see Fig.12 .

[0139] Comparative Example 10:

[0140] Compared with Example 1, the treatment process of this comparative example remains unchanged, and the ingredients and concentrations of component A and component C remain unchanged. The difference is that the amount of succinic acid in component B is reduced to 70 ml.

[0141] From the results of the salt spray test, it can be seen that since the amount of succinic acid in component B in this comparative example is reduced, the complexing ability with chromium ions in the solution is reduced, the film forming speed is reduced, and the stability and corrosion resistance of the film layer are deteriorated. After 48 hours of the salt spray test, reddish-brown rust appears on six sides of the bolt head. Fig.13 Among them, the upper and lower groups are the hexagon head bolts before and after the dry-wet alternating salt spray test.

[0142] Comparative Example 11:

[0143] Compared with Example 1, the treatment process of this comparative example remains unchanged, the ingredients and concentrations of component A and component C remain unchanged, and the difference is that the amount of sodium dodecyl sulfate in component B is reduced to 20 ml.

[0144] From the results of the salt spray test, it can be seen that in this comparative example, the amount of sodium dodecyl sulfate in component B is reduced, resulting in poor wetting performance of the solution. The cross groove of the bolt head is the part most likely to retain metal impurities during processing. The metal impurities are not completely removed. After 48 hours of the salt spray test, reddish-brown rust appears in the cross groove of the bolt head. See Fig.14 Among them, the upper and lower groups are the hexagon head bolts before and after the dry-wet alternating salt spray test.

[0145] Comparative Example 12:

[0146] Compared with Example 2, the treatment process of this comparative example remains unchanged, the ingredients and concentrations of component A and component B remain unchanged, and the difference is that the ratio of barium petroleum sulfonate to N-oleoyl sarcosine octadecanoic acid ammonium in component C is changed, wherein the amount of barium petroleum sulfonate is increased to 110 ml, and the amount of N-oleoyl sarcosine octadecanoic acid ammonium is reduced to 90 ml.

[0147] In component C of the present invention, the ratio of barium petroleum sulfonate to octadecanoyl sarcosine is 1:1.1 to 1:1.5; since the ratio of barium petroleum sulfonate to octadecanoyl sarcosine in component C in this comparative example is changed and is not within the ratio range of barium petroleum sulfonate to octadecanoyl sarcosine in component C of the present invention, the emulsification effect of the solution is poor. It can be seen from the operation process that a thick oil film is formed on the surface of the product, which affects the appearance of the product. See Fig.15 .

[0148] Comparative Example 13:

[0149] Compared with Example 1, the treatment process of this comparative example remains unchanged, the ingredients and concentrations of component A and component B remain unchanged, and the difference is that the amount of nonylphenol polyoxyethylene ether in component C is reduced to 30 ml.

[0150] It can be seen from the solution preparation process that in this comparative example, the amount of nonylphenol polyoxyethylene ether in component C is reduced, resulting in poor emulsification of the solution and stratification of component C. Fig.16 .

[0151] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A solution for improving the corrosion resistance of fasteners made of PH13-8Mo material, characterized in that: It includes component A, component B and component C, and the parts are immersed in component A, component B and component C in sequence; In terms of mass percentage, the component A includes: 35-40% nitric acid; 3-5% corrosion inhibitor; 3-5% stabilizer; 2-4% surfactant; 2-4% dispersant; and the remainder solvent; In terms of mass percentage, the component B includes: 5-10% boric acid; 10-15% film former; 8-10% complexing agent; 8-10% oxidant; 5-10% thickener; 3-5% wetting agent; and the remainder of solvent; Calculated by mass percentage, the component C includes: 4-8% emulsifier; 12-15% surfactant; 18-25% rust inhibitor; and the remainder solvent; In the component A, the corrosion inhibitor is ammonium nitrate; the stabilizer is citric acid; the surfactant is sodium fatty alcohol polyoxyethylene ether sulfate; and the dispersant is acetylene glycol; In the component B, the film-forming agent is chromium nitrate; the complexing agent is succinic acid; the oxidant is sodium nitrate; the thickener is triethanolamine; and the wetting agent is sodium dodecyl sulfate; In the component C, the emulsifier is nonylphenol polyoxyethylene ether; the surfactant is polyoxyethylene fatty alcohol ether; the rust inhibitor is barium petroleum sulfonate and N-oleoyl sarcosine octadecanoic acid ammonium salt, and the ratio of barium petroleum sulfonate to N-oleoyl sarcosine octadecanoic acid ammonium salt is 1:1.1 to 1:1.5; The solvent is water.

2. A process for improving the corrosion resistance of fasteners made of PH13-8Mo material, characterized in that: Using the solution for improving the corrosion resistance of fasteners made of PH13-8Mo material as claimed in claim 1; The specific steps include: (1) Place the parts in a perforated container and soak the container in component A at room temperature, with a soaking temperature of 45°C-55°C and a soaking time of 30min-40min. Shake the container 3-4 times during the soaking period. (2) Use running cold water to clean the residual component A on the surface of the parts, shaking the container for 0.5 min to 1.0 min; (3) Immerse the parts in deionized water, shaking the container for 0.5 min to 1.0 min; (4) First use compressed air to clean the surface water of the parts, and then dry them at a temperature of 80°C-100°C for 20min-30min; (5) Soak the parts in component B at a temperature of 60°C-70°C for 15-20 minutes, shaking the container 3-4 times during the soaking period; (6) Use running cold water to clean the component B remaining on the surface of the parts, shaking the container during the process, for 1.0 min to 3.0 min; (7) Immerse the parts in deionized water, shaking the container for 1.0 min to 3.0 min; (8) First use compressed air to clean the surface water of the parts, and then dry them at a temperature of 130°C-135°C for 15min-20min; (9) Soak the parts in component C for 2-3 minutes, shaking the container 1-2 times during the soaking period; (10) Place the parts in an oven at a drying temperature of 80°C-120°C and a drying time of 20 min-30 min.

3. The process for improving the corrosion resistance of fasteners made of PH13-8Mo material according to claim 2, characterized in that: The container is a titanium basket.

4. The process for improving the corrosion resistance of fasteners made of PH13-8Mo material according to claim 2 or 3, characterized in that: In step (1), the amount of parts loaded is less than or equal to 1 / 3 of the container volume.

5. The process for improving the corrosion resistance of fasteners made of PH13-8Mo material according to claim 2, characterized in that: In step (4) and step (8), the parts are dried in an electric heated air drying oven.

Citation Information

Patent Citations

  • Aluminium alloy trivalent chromium passivation solution as well as preparation method and passivation technology thereof

    CN102912338A

  • Water-based environmental protection rust inhibitor for steel parts, and preparation method and application of water-based environmental protection rust inhibitor

    CN107299338A